Duoplasmatron beam characteristic in an ion source test stand for an accelerator mass spectrometer. (June 2019) - Park, Sae-Hoon; Lee, Sang-Hun; Kim, Yu-Seok
Abstract: A gaseous ion source has been designed at Dongguk University accelerator mass spectrometer facility, Korea. Radiocarbon dating is conducted at this facility with a mini carbon dating system and a prototype ion source has been developed for a gas injection system for high-level 14 C samples, which can decrease the precision of sample measurements for carbon dating. To improve the efficiency of carbon counting of gas samples, a gaseous ion source called a duoplasmatron has been installed in the prototype ion source test stand with low cost, easy maintenance, and direct gas discharge. It is necessary to verify the operation characteristics of the duoplasmatron of the ion source test stand with the beam characteristics to measure the beam current with various ion source parameters. The effects of the arc current, ion source magnet field, and extraction voltage on the beam current are presented in this paper. Highlights: Total beam current increased as the applied voltage increased. Most arc currents show decreasing beam current as the ion source magnet increased. Intermediate electrode and anode center hole distance can affect plasma density.